Penyuluhan Pemberian Ampas Tahu dan Gamal Dalam Ransum untuk Meningkatkan Bobot Badan Domba di Desa Ciakar Kecamatan Cijulang Kabupaten Pangandaran - Cikal Beni Nata; Wahyuningsih; Arifin Tasrif (Jurnal Penyuluhan Pertanian, 2022)
The use of tofu and Gamal dregs in sheep rations for breeders in Ciakar village is not widely known. Therefore, the objective of this study is to see the extent of knowledge and skills in adopting simple technology regarding the use of tofu and Gamal dregs in sheep feed rations and increasing daily body weight (PPBH) of sheep. The study was carried out from April 5 to June 28, 2021. The treatment was given various doses of tofu and Gamal dregs to the daily weight gain of sheep and a questionnaire to see the level of knowledge and skills of sheep breeders using the additional feed. The results showed that the use of tofu and Gamal dregs was able to increase the PBBH by 171.5 g/head/day compared to the control (without giving tofu and Gamal dregs). In addition, the level of knowledge and skills of farmers increased by 52.88% and skills by 51.29% with the criteria of success for the adoption of simple technology using additional feed tofu dregs and Gamal in sheep feed rations.